HDL and persistent inflammation immunosuppression and catabolism syndrome - Barker, Grant; Winer, Julia R; Guirgis, Faheem W; Reddy, Srinivasa (Current opinion in lipidology, 2021)
This study reviews the mechanisms of HDL cholesterol immunomodulation in the context of the mechanisms of chronic inflammation and immunosuppression causing persistent inflammation, immunosuppression and catabolism syndrome (PICS) and describes potential therapies and gaps in current research. Low HDL cholesterol is predictive of acute sepsis severity and outcome. Recent research has indicated apolipoprotein is a prognostic indicator of long-term outcomes. The pathobiologic mechanisms of PICS have been elucidated in the past several years. Recent research of the interaction of HDL pathways in related chronic inflammatory diseases may provide insights into further mechanisms and therapeutic targets. HDL significantly influences innate and adaptive immune pathways relating to chronic disease and inflammation. Further research is needed to better characterize these interactions in the setting of PICS.